Measurement and Evaluation of Macroeconomic Stability in Poland - Janecki, Jarosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The aim of this paper is to evaluate the macroeconomic stability in Poland. First of all, there was presented scoreboard for the surveillance of macroeconomic imbalances presented by the European Commission (EC) in the Alert Mechanism Report. The EC publish annually set of indicators, together with recommendations for individual EU Member States. The paper presents the details of this this approach, together with an assessment for Poland. Secondly, there was presented method of calculations of macroeconomic stability – the macroeconomic stabilization pentagon (PSM). According to our calculations, PSM method indicates that in the year of 2015, Poland’s economy was the most stable economy since the financial crisis in 2018 (total internal and external stability). Both calculations methods suggest no macroeconomic imbalances in Poland, which confirms the macroeconomic stability in Poland.